(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses a comparative study of the choice of the type of racks of the working parts of a chisel-cultivator. In bench tests, each rack was fixed to a special frame; a static load was applied to them, simulating the resultant force of soil resistance. At each loading stage , movements of the toe of the paw were measured. In addition, the agro -energy performance indicators of the chisel-cultivator with various stands were studied. By results research selected spiral elastic stand